Comparative Study of the Effect of Baicalin and Its Natural Analogs on Neurons with Oxygen and Glucose Deprivation Involving Innate Immune Reaction of TLR2/TNFα. (21st March 2012) - Li, Hui-Ying; Hu, Jun; Zhao, Shuang; Yuan, Zhi-Yi; Wan, Hong-Jiao; Lei, Fan; Ding, Yi; Xing, Dong-Ming; Du, Li-Jun
Abstract : This work is to study the baicalin and its three analogs, baicalin, wogonoside, and wogonin, on the protective effect of neuron from oxygen-glucose deprivation (OGD) and toll-like receptor 2 (TLR2) expression in OGD damage. The results showed that baicalin and its three analogs did protect neurons from OGD damage and downregulated protein level of TLR2. D-Glucopyranosiduronic acid on site 7 in the structure played a core of cytotoxicity of these flavonoid analogs. The methoxyl group on carbon 8 of the structure had the relation with TLR2 protein expression, as well as the anti-inflammation. In addition, we detected caspase3 and antioxidation capability, to investigate the effect of four analogs on cell apoptosis and total antioxidation competence in OGD model.